The Impact of STEM-based Interactive Multimedia on Vibrations and Waves to Improve Students’ Critical Thinking Skills and Learning Independence - Samihah, Ismalida Maftuhatus; Wiyanto, Wiyanto; Widiyatmoko, Arif; Rusilowati, Ani; Satono, Sigit (Journal of Innovative Science Education, 2024)
Indonesia implements the Merdeka Curriculum, which focuses on cultivating Pancasila education. The dimensions of the Pancasila student profile consist of critical and independent thinking, which are also found in the 21st-century skills, and STEM-based learning may be one of the solutions to improving the two dimensions. This research aims to unveil the impact of applying STEM-based interactive multimedia on vibrations and waves, particularly in improving students' critical thinking skills and learning independence. The method was experimental research with a nonequivalent group pretest-posttest design, in which the experimental class used STEM-based interactive multimedia while the control class used PowerPoints. Experts validated the multimedia and instrument before the implementation, and the effectivity was measured using the t-test. The results revealed that the multimedia effect on critical thinking skills scored 5.6763 t-count > 2.0025 t-table, while the impact on learning independence was 7.3462 t-count > 2.0025 t-table. The outcomes show significant differences between the experimental and control classes; therefore, we conclude that STEM-based interactive multimedia is effective in improving critical thinking skills and learning independence.